Peningkatan Pengetahuan Bahaya Anemia pada Remaja Putri dengan Edukasi Penggunaan Tablet Tambah Darah - Della Jauharotus Sa’adah; Hasna Mawar Halimah; Maria Yustati Lele; Melati Aprilliana Ramadhani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Adolescence is a transitional period from childhood to adulthood, typically encompassing ages 10 to 19 years, marked by significant physical, psychological, and social changes. Anemia constitutes a major health concern among adolescents, particularly female adolescents. Anemia is defined as a condition where hemoglobin (Hb) levels in the blood are below the normal range, primarily due to iron (Fe) deficiency. This deficiency negatively affects growth, development, cognitive abilities, and learning concentration, while simultaneously increasing susceptibility to infectious diseases and the risk of future reproductive complications. To enhance adolescents' comprehension of the dangers of anemia, an intervention was implemented through health education (counseling). This activity encompassed material presentation, distribution of educational leaflets on anemia, interactive discussion/question-and-answer sessions, and instruction on the proper use of Iron Supplement Tablets (TTD - Tablet Tambah Darah). Iron Supplement Tablets are a nutritional supplement containing iron and folic acid, essential for the body to produce healthy red blood cells and prevent anemia. The target participants for this counseling session were female adolescents at SMK Kanisius Ungaran (Kanisius Ungaran Vocational High School). It is vital for these adolescents to receive engaging and educational information to prevent and manage the risks associated with anemia. A post-intervention evaluation, measured through pretest and posttest scores, demonstrated an increase in knowledge following the education session. The pretest yielded an average score of 68.23. However, following the provision of counseling, the posttest results showed a significant increase, with an average score of 87.86.   ABSTRAK Remaja putri adalah masa transisi dari anak-anak menuju dewasa dengan rentang usia sekitar 10 hingga 19 tahun yang ditandai dengan berbagai perubahan signifikan, baik secara fisik, psikologis, maupun sosial dengan masalah anemia yang menjadi fokus utama pada remaja. Anemia adalah kondisi dimana hemoglobin (Hb) dalam darah kurang dari normal yang disebabkan karena kekurangan zat besi (Fe) yang berdampak negatif pada pertumbuhan, perkembangan, kemampuan kognitif dan konsentrasi belajar, serta meningkatkan kerentanan terhadap penyakit infeksi dan risiko kompikasi reproduksi di masa depan. Dalam meningkatkan pemahaman remaja tentang bahaya anemia dilakukan salah satu upaya melalui penyuluhan dengan pemaparan materi, pembagian leaflet edukasi anemia, diskusi/tanya jawab dan pemberian edukasi penggunaan Tablet Tambah Darah (TTD). Tablet tambah darah adalah suplemen gizi yang mengandung zat besi dan asam folat yang dibutuhkan tubuh untuk memproduksi sel darah merah yang sehat dan mencegah anemia. Sasaran penyuluhan ini adalah para remaja putri SMK Kanisius Ungaran. Pentingnya bagi para remaja putri SMK Kanisius Ungaran untuk mendapatkan informasi yang menarik dan edukatif untuk mencegah dan mengatasi bahaya anemia pada remaja. Adanya peningkatan pengetahuan setelah diberikannya penyuluhanyang dilihat dari hasil pretest dan posttest setelah pemaparan materi. Hasil pretest diperoleh skor rata-rata 68,23. Namun, setelah diberikan penyuluhan terjadi peningkatan dengan hasil posttest dengan skor rata-rata 87,86.